2016 23rd International Symposium on Temporal Representation and Reasoning (TIME) 2016
DOI: 10.1109/time.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Timelines Are Expressive Enough to Capture Action-Based Temporal Planning

Abstract: Abstract-Planning problems are usually expressed by specifying which actions can be performed to obtain a given goal. In temporal planning problems, actions come with a time duration and can overlap in time, which noticeably increase the complexity of the reasoning process. Action-based temporal planning has been thoroughly studied from the complexity-theoretic point of view, and it has been proved to be EXPSPACEcomplete in its general formulation. Conversely, timelinebased planning problems are represented as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…A fair empirical comparison to FAPE is not possible here, due to the difference in representation language, and the HTN planning approach. Finally, we note that other researchers (Gigante et al 2016) have shown that timeline based languages are able to express PDDL problems, which is the complement of our work.…”
Section: Other Related Worksupporting
confidence: 56%
“…A fair empirical comparison to FAPE is not possible here, due to the difference in representation language, and the HTN planning approach. Finally, we note that other researchers (Gigante et al 2016) have shown that timeline based languages are able to express PDDL problems, which is the complement of our work.…”
Section: Other Related Worksupporting
confidence: 56%
“…The computational complexity of other planning formalisms has been studied before, from classical (Bylander 1994) to hierarchical (Erol, Hendler, and Nau 1996), to timeline-based planning (Gigante et al 2016;2017). When comparing our results with the timeline-based planning paradigm in particular, it is interesting to note a similar complexity jump, with a problem that is EXPSPACE-complete over discrete time (Gigante et al 2017), but becomes undecidable over dense time (Bozzelli et al 2018).…”
Section: Related Workmentioning
confidence: 99%
“…-Reasoning about time requirements: Although both paradigms are able to explicitly take time into account when creating the plans, it has been demonstrated that timeline-based planning is expressive enough to capture actionbased temporal planning, while the contrary is yet unclear [13]. If complex temporal reasoning is needed, as in the case of quantitative temporal relations among goals (for example representing that a goal must be achieved between 10 and 15 s after another goal has been reached), timeline-based planning is usually a better approach.…”
Section: Selection Of the Planning Paradigmmentioning
confidence: 99%